Analysis of water based Casson hybrid nanofluid (NiZnFe2O4+MnZnFe2O4) flow over an electromagnetic actuator with Cattaneo–Christov heat-mass flux: A modified Buongiorno model - S. Baskaran; R. Sowrirajan; S. Divya; S. Eswaramoorthi; K. Loganathan (Partial Differential Equations in Applied Mathematics)
The Casson hybrid nanofluid has pivotal role in boosting heat transfer capableness in several industrial and technological applications. In light of this consideration, the current inquisition examined the Darcy–Forchheimer flow of a water-based mono nanofluid (NiZnFe2O4) and hybrid nanofluid (NiZnFe2O4+MnZnFe2O4) past a stretched Riga plate with Cattaneo–Christov heat-mass flux and nonlinear radiation. Additionally, this inspection focuses on analyzing the upshot of heat generation/absorption, Brownian motion, thermophoresis, and Lewis number. Using suitable variables, the governing coupled nonlinear partial differential equations are transformed into ordinary differential equations, which are solved using MATLABs bvp4c solver. The implication of key parameters on both direction velocities, temperature, nanofluid concentration, skin friction coefficients, local Nusselt number, and Sherwood number are displayed graphically. Our investigation revealed that fluid velocities are suppressed by increasing the values of Forchheimer number. The temperature profile grows when magnifying the values of Brownian motion and thermophoresis parameters. The Lewis number and mass relaxation time parameter declines the nanofluid concentration profile. The surface shear stress slumps when upgrades the Casson parameter and porosity parameter. The heat transfer rate enriches when elevating the quantities of radiation parameter and Biot number. Brownian motion and thermophoresis parameters reduce the mass transfer rate.